2019
DOI: 10.4049/jimmunol.1900408
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 Is a Cell-Intrinsic Regulator of Fitness during Early B Cell Development

Abstract: IL-33 is an IL-1 family member protein that is a potent driver of inflammatory responses in both allergic and nonallergic disease. This proinflammatory effect is mediated primarily by extracellular release of IL-33 from stromal cells and binding of the C-terminal domain of IL-33 to its receptor ST2 on targets such as CD4+ Th2 cells, ILC2, and mast cells. Notably, IL-33 has a distinct N-terminal domain that mediates nuclear localization and chromatin binding. However, a defined in vivo cell-intrinsic role for I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 49 publications
(66 reference statements)
1
21
0
Order By: Relevance
“…Evidence for a nuclear role for IL‐33 has been put forward mainly using cultures of epithelial and endothelial cell lines where IL‐33 knockdown strategies led to changes in the expression of selected genes [1012, 21], with other studies on similar cells coming to the opposite conclusion, including in more global transcriptomic and proteomic approaches highlighting the ST2 dependence of IL‐33‐mediated effects on transcription [14, 15]. More recently, the first ex vivo study with cells isolated from WT and Il33 −/− mice was reported [16]. It indicates a cell‐intrinsic role for IL‐33 as negative regulator of pro‐B‐cell development and fitness with distinct differences observed at the transcript level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence for a nuclear role for IL‐33 has been put forward mainly using cultures of epithelial and endothelial cell lines where IL‐33 knockdown strategies led to changes in the expression of selected genes [1012, 21], with other studies on similar cells coming to the opposite conclusion, including in more global transcriptomic and proteomic approaches highlighting the ST2 dependence of IL‐33‐mediated effects on transcription [14, 15]. More recently, the first ex vivo study with cells isolated from WT and Il33 −/− mice was reported [16]. It indicates a cell‐intrinsic role for IL‐33 as negative regulator of pro‐B‐cell development and fitness with distinct differences observed at the transcript level.…”
Section: Discussionmentioning
confidence: 99%
“…Yet another study described the overexpression of IL‐33 in an epithelial cell line with no transcriptional changes observed in a genome‐wide analysis [15]. So far, only one recent study compared ex vivo cells, namely wt versus Il33 −/− pro‐B cells, and uncovered many transcriptional changes in absence of IL‐33 with mixed BM chimera experiments indicating these effects are cell intrinsic [16]. Together, these data suggest that IL‐33 can regulate gene transcription but that this property is cell‐type and context‐dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Vaccines 2020, 8, x 6 of 25 [97] and also functions as a cell-intrinsic regulator of fitness during the early development of B-cells [98]. Not all inflammasome substrates are pro-inflammatory.…”
Section: Inflammasome-mediated Activation Of Adaptive Immunitymentioning
confidence: 99%
“…In the adaptive immune system, ST2 has been shown to be preferentially expressed by Th2 cells, where IL-33 stimulation has been shown to induce the production of IL-4, IL-5 and IL-13 (Schmitz et al, 2005;Paul and Zhu, 2010). IL-33 has also been shown to suppress T helper type 1 (Th1) responses (Rostan et al, 2013;Stier et al, 2019), though some studies have shown that it may potentiate Th1 responses as well in an IL-12 dependent manner (Smithgall et al, 2008;Komai-Koma et al, 2016). A compiled meta-analysis study of the IL-33/ST2 axis has revealed the enormous extent of the complexity and involvement of this signaling pathway, revealing just how much remains to be understood (Pinto et al, 2018).…”
Section: Introductionmentioning
confidence: 99%